Policy choice in time series by empirical welfare maximization - Toru Kitagawa; Weining Wang; Mengshan Xu (Centre for Microdata Methods and Practice (cemmap), 2024)
This paper develops a novel method for policy choice in a dynamic setting where the available data is a multi-variate time series. Building on the statistical treatment choice framework, we propose Time-series Empirical Welfare Maximization (T-EWM) methods to estimate an optimal policy rule by maximizing an empirical welfare criterion constructed using nonparametric potential outcome time series. We characterize conditions under which T-EWM consistently learns a policy choice that is optimal in terms of conditional welfare given the time-series history. We derive a nonasymptotic upper bound for conditional welfare regret. To illustrate the implementation and uses of T-EWM, we perform simulation studies and apply the method to estimate optimal restriction rules against Covid-19.
Keywords: 330; Causal inference; potential outcome time series; treatment choice; regret bounds; concentration inequalities